Build a distributed IoT Cluster on .NET 6 : using Blazor and SignalR to manage IoT devices (Apress, 2022)
This video will teach you how to build a cluster of IoT devices using only .NET components. After viewing it you will be able to build a complete distributed IoT solution using .NET 6, SignalR and Blazor. This videos explains how SignalR can substantially simplify two-way real-time communication between the server and its clients. Viewers will learn how to build and manage clusters of IoT devices using only .NET and will see, by example, how to build an IoT device management web interface without having to learn JavaScript